2021
DOI: 10.1152/ajpendo.00410.2020
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of a ketogenic diet and exercise training alter mitochondrial and peroxisomal substrate oxidative capacity in skeletal muscle

Abstract: Ketogenic diets (KD) are reported to improve body weight, fat mass, and exercise performance in humans. Unfortunately, most rodent studies have used a low-protein KD, which does not recapitulate diets used by humans. Since skeletal muscle plays a critical role in responding to macronutrient perturbations induced by diet and exercise, the purpose of this study was to test if a normal-protein KD (NPKD) impacts shifts in skeletal muscle substrate oxidative capacity in response to exercise training (ExTr). A high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 88 publications
(126 reference statements)
0
26
0
Order By: Relevance
“…They found that overexpression of PGC-1α induced the expression of AOCX1, and that the levels of some proteins associated with peroxisome activity also substantially increased [87]. In addition, some studies have also demonstrated the importance of PGC-1α in peroxisomes [88,89].…”
Section: Pgc-1αmentioning
confidence: 99%
“…They found that overexpression of PGC-1α induced the expression of AOCX1, and that the levels of some proteins associated with peroxisome activity also substantially increased [87]. In addition, some studies have also demonstrated the importance of PGC-1α in peroxisomes [88,89].…”
Section: Pgc-1αmentioning
confidence: 99%
“…The majority of studies conducted on rodents have used a low-protein KD. As such, recently, Huang et al ( 143 ) investigated the possible alterations of a normal-protein KD (NPKD) upon the substrate oxidative capacity in the skeletal muscle of C57BL/6 male mice which were also introduced to an exercise training regime. The application of NPKD or exercise training alone could not produce changes in the mitochondrial content, while their combined application was found to increase both mitochondrial fission/fusion markers and PGC-1α levels.…”
Section: Dietsmentioning
confidence: 99%
“…The favorable changes in body composition from KDs appear to be influenced by the degree of nutritional ketosis achieved [ 85 ]. KDs may exert a protective effect against muscle mass loss, potentially through maintenance rather than a net hypertrophic effect [ 84 ].…”
Section: Ketogenic Diet In Cachexiamentioning
confidence: 99%
“…CR facilitates mitochondrial fat oxidation in SKM through upregulated AMPK signaling, working in opposition to IGF-1-mediated activation of mTOR [ 111 ]. KDs may contribute to SKM maintenance or growth through upregulation of mTOR signaling [ 85 , 112 ]. Huang et al showed that a normal-protein KD activated mTOR-related proteins that drive protein synthesis over autophagy [ 85 ].…”
Section: Cellular Mechanisms Of Kds In Pdac and Cachexiamentioning
confidence: 99%
See 1 more Smart Citation